Nutritional Status and Morbidity of Children Aged 12 to 59 Months in the Peri-urban Area of Kisangani, Democratic Republic of Congo - Gaston Boande; Raphael Iseayembele; Rachel Olonga; Véronique Mokoto; Franc Esuka; Alliance Tagoto; Eugene Basandja; John Panda; Emmanuel Tebandite; Joris Losimba (Journal of Food Innovation, Nutrition, and Environmental Sciences)
This study describes the nutritional status and prevalence of common childhood illnesses of children aged 12 to 59 months in the peri-urban area of Kisangani, DRC.  A descriptive cross-sectional study was conducted from June 15 to July 15, 2024, involving 850 children and their mothers. A multi-stage cluster sampling method was used to select households. Data were collected via face-to-face interviews, anthropometric measurements (weight, height, mid-upper arm circumference), and recorded in Kobotoolbox. Anthropometric data were converted into indices using WHO AnthroPlus software, with Z-scores for weight-for-height (WHZ), height-for-age (HAZ), and weight-for-age (WAZ) calculated based on the WHO Multicentre Growth Reference Standards. Nutritional status was classified using Z-scores, with values below −2 standard deviations indicating wasting (WHZ), stunting (HAZ), or underweight (WAZ). Statistical analyses were conducted using Stata version 13 software. Among the 850 children, 8.1% had wasting, 40.2% stunted growth, and 19.2% were underweight. Mothers under 30 years old accounted for 63.5%, and 58.9% had at least a secondary education. Unsafe drinking water affected 55.9% of households, and 75.8% had unimproved sanitation. The prevalence of measles, ARI, diarrhea, and fever was 23.2%, 26.7%, 19.5%, and 48.1%, respectively. Malnutrition was significantly associated (p<0.05) with male gender, lack of income, unsafe water, unimproved sanitation, measles, diarrhea, and vaccination status. The results emphasize the importance of improving access to clean water, vaccination, and sanitation infrastructure for reducing childhood malnutrition and limiting waterborne and infectious diseases.